Extract Enriched in Flavan-3-ols and Mainly Procyanidin Dimers Improves Metabolic Alterations in a Mouse Model of Obesity-Related Disorders Partially via Estrogen Receptor Alpha - Leonetti, Daniela; Soleti, Raffaella; Clere, Nicolas; Vergori, Luisa; Jacques, Caroline; Duluc, Lucie; Dourguia, Catherine; Martínez, Maria C.; Andriantsitohaina, Ramaroson (Frontiers in Pharmacology, 2018)
Red wine polyphenol extracts improve cardiovascular and metabolic disorders linked to obesity. Their vascular protection is mediated by the activation of the alpha isoform of the estrogen receptor (ERα). In the present study, we explored the effects of a grape seed extract (GSE) enriched in the flavan-3-ols procyanidin dimers on obesity-related cardiovascular and metabolic disorders; with a particular interest in the role/contribution of ERα. Ovariectomized wild type or ERα knockout (KO) mice were fed with standard or western diet, supplemented or not with GSE, for 12 weeks. Their body weight was monitored throughout the study, and an echocardiography was performed at the end of the treatment. Blood and tissues were collected for biochemical and functional analysis, including nitric oxide and oxidative stress measurement. Vascular reactivity and liver mitochondrial complexes activity were also analyzed. In western diet-fed mice, GSE reduced adiposity, plasma triglycerides and oxidative stress in the heart, liver, adipose and skeletal tissues; but did not improve the vascular dysfunction. In western diet-fed mice, ERα deletion prevented or reduced the beneficial effects of GSE on plasma triglycerides and visceral adiposity. ERα deletion also prevented/reduced the anti-oxidant effect of GSE in the liver, but did not affect its capacity to reduce oxidative stress in the heart and adipose tissue. In conclusion, dietary supplementation of GSE attenuated features of metabolic syndrome partially through ERα-dependent mechanisms. This report highlights the therapeutic potential of polyphenols, and especially extract enriched in procyanidin dimers, against the metabolic disorders associated with excessive energy intake.